METAFORA ORIENTASIONAL DALAM BULETIN HALO JEPANG (KAJIAN SEMANTIK KOGNITIF) - Nunik Nur Rahmi Fauzah (Faculty of Economics, Law, and Humanities, 2020)
This research is about orientational metaphor in Bulletin Halo Jepang. According to Lakoff and Johson (1980) orientational metaphor is one of parts from conceptual theory. The source of data is Bulletin Halo Jepang edition in July and August 2017. This research used qualitative method and descriptive analysis to analyse the data. The aim is to describe all concepts of source domain (B) and target domain (A) that expressed temporarily. It is showed with up and down level, inside and outside, front and backward, open and close, deep and short. The total of data is 10 sentences with orientational metaphor. The result showed that 2 data of down, 4 data of up, 1 data of front, 1 data of outside and 2 data of deep.